1999
DOI: 10.1002/hep.510290612
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Iron Overload and Induced Lipid Peroxidation Are Associated With Impaired Plasma Lipid Transport and Hepatic Sterol Metabolism in Rats

Abstract: Although hemochromatosis is characterized by dramatic morphological and functional alterations in the liver, little is known about the effects of an excess of iron on lipid metabolism. Therefore, we determined the effect of chronic iron overload on plasma lipid profile and lipoprotein composition, as well as on hepatic cholesterol metabolism and biliary sterol output. Rats administered a diet enriched with 3% iron carbonyl for 12 weeks displayed a 30-fold increase in iron (P F .0001) and a 5-fold rise in malon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 53 publications
(66 reference statements)
5
70
1
1
Order By: Relevance
“…Caco-2 cells were cultured in the presence or absence of Fe 2ϩ /ascorbate (0.2:2 mM; Sigma, St. Louis, MO) for periods varying between 1 and 24 h. The amount of free malondialdehyde (MDA) formed during the reaction was determined by HPLC, as we previously described (6). Proteins were first precipitated with a 10% sodium tungstate (Na 2WO4) solution (Aldrich, Milwaukee, WI).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Caco-2 cells were cultured in the presence or absence of Fe 2ϩ /ascorbate (0.2:2 mM; Sigma, St. Louis, MO) for periods varying between 1 and 24 h. The amount of free malondialdehyde (MDA) formed during the reaction was determined by HPLC, as we previously described (6). Proteins were first precipitated with a 10% sodium tungstate (Na 2WO4) solution (Aldrich, Milwaukee, WI).…”
Section: Methodsmentioning
confidence: 99%
“…Given this mounting evidence for prooxidant role of ascorbate in the presence of redoxactive transition metal ions, we previously used the Fe 2ϩ / ascorbate system to investigate the repercussions of lipid peroxidation on lipid metabolism. We found that iron/ascorbate-induced peroxidation provoked profound perturbations in lipid transport, apoprotein biogenesis, lipoprotein assembly, and sterol regulatory enzymes, which play a critical role in cholesterol homeostasis (6,7,9).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Em estudo anterior do nosso laboratório, demonstrou-se aumento significativo da concentração de Fe no fígado (cerca de 12,2 % em relação ao grupo controle) após 90 dias de consumo de rações com moderada sobrecarga de Fe (550 mg/kg) (COCATO, 2008). Outros estudos demonstraram aumento da concentração hepática de Fe proporcional à concentração na ração em intervalo variando de 3 mg a 1500 mg de Fe/kg de ração (WARD et al, 1991;DABBAGH et al, 1994;BRUNET et al, 1999;WHITTAKER e CHANDERBHAN, 2001;COCKELL et al, 2005. As análises histológicas para se avaliar a distribuição do depósito (DABBAGH et al, 1994;BRUNET et al, 1999;WHITTAKER, CHANDERBHAN, 2001;LAFAY et al, 2005). No entanto, nas condições experimentais do presente estudo, não foram observadas alterações nas transaminases e no perfil lipídico sérico bem como no perfil de ácidos graxos no fígado, sugerindo uma eventual proteção antioxidante nesse compartimento (Tabelas 4 e 8).…”
Section: Medula óSseaunclassified
“…The mutation of the HFE gene leading to hereditary haemochromatosis has been one factor which has been implicated in NAFLD disease progression (6,119,121) and iron overload has been associated with oxidative stress and altered lipid and glucose metabolism (259). Previous studies from our laboratory have shown increased disease severity -steatohepatitis and necroinflammation -in Hfe knockout mice fed a high calorie diet.…”
Section: Development Of An In Vitro Model To Investigate Iron Loadingmentioning
confidence: 99%